Effect of machining parameters on surface textures in wire electro discharge machining of aisi 4140 steel - Nurul Shazwani, Mehat (2008)
The Wire Electro Discharge Machining (WEDM) process is a violent thermal process where literally thousands of electrical discharges are produced in a fraction of a second in order to erode a certain volume of metal. The process is most used in situations where intricate complex shapes need to be machined in very hard materials (such as hardened tool steel). However, the process generates surface that have poor properties such as high tensile residual stresses, high surface roughness, presence of micro-cracks and micro-voids. These properties vary with different levels of the main machining parameters. The aim of this paper is to present experimental work that has been done in order to quantify the effect of some of the main WEDM parameters on the surface texture. 2D surface measurements were taken on all WEDM samples and 2D surface characterization has been carried out in order to calculate the different surface texture parameters. In this work, the surface characteristics caused by WEDM were analyzed by Scanning Electron Microscopy (SEM). An empirical model of AISI 4140 steel was proposed based on the experimental data. Surface roughness was determined with a ‘Perthometer’ recorder. Experimental results indicate that the WEDM process causes a ridged surface and induces machining damage in the surface layer and increases the surface roughness. The depth of micro-cracks and micro-voids increases with an increase in the amount of pulsed current and pulse-on duration. The effect of the magnitude of the pulse-on duration on the surface texture of the specimen is more significant than the pulsed current. Furthermore, the SEM reveals the two-dimensional image of surface textures of the WEDM specimen with a nanometer scale.